Direct Versus Indirect Bypass in Early-Stage Moyamoya (Suzuki I-III): A Propensity Score-Weighted Study - Basel Musmar; Joanna M. Roy; Hammam Abdalrazeq; Victor Gabriel El-Hajj; Michael Rizzuto; Matthews Lan; Pious Patel; Michael Baldassari; Arbaz Momin; Yazan Shamli Oghli; Marissa Tucci; Joseph Schaefer; et al. (Translational Stroke Research, 2026)

Assessment of two minimally invasive methodologies for sex identification in the European eel, Anguilla anguilla - Michael J. Williamson; Jack A. Brand; Kevin Hopkins; Luke O'Connor; Matthew W. Perkins; Christopher Sergeant; Simon Spiro; Taina Strike; Jessica Whinfield; Rosie S. Williams; Ethan Wrigglesworth; Rosalind M. Wright; et al. (Journal of Fish Biology, 2026)
Sex is an important driver of variation in behaviour, ecology and physiology. Sex identification in the Critically Endangered European eel ( Anguilla anguilla ) currently requires fish sacrifice, or the use of morphological differences such as body length, which can be inaccurate in certain habitats and at intermediate body lengths. Non‐lethal tools for accurate sex identification in this species are therefore required. Here, we test the efficacy of two minimally invasive methods of sex identification: (1) ultrasonography and (2) molecular markers taken from pectoral fin clips. Both methodologies were applied to riverine European silver eel and compared to histological sex identification. Ultrasonography accurately identified the gonads in female eel, with males identified by the absence of detectable gonadal structures. The level of expression of three molecular markers ( dcn, LOC111853410 , kera ) previously used to identify sex in Japanese eel ( Anguilla japonica ) were evaluated. There was no significant differential expression of the three molecular markers between sexes, suggesting that these markers cannot be accurately used to identify sex in European eel. Our findings suggest that minimally invasive imaging using ultrasonography can be a reliable tool for identifying sex in early‐stage adult migratory European eels, with particular use at intermediate sizes (400–500 mm) and animals in habitats where migration potential is limited and may regularly exceed typical growth sizes. This technique can be highly valuable for studies that address ecological, behavioural, conservation and management issues in this Critically Endangered species.

Improving eel pass efficiency: The role of crest shape and water flow in facilitating upstream juvenile eel migration - Michael J. Williamson; Bryony E. Allen; Jack A. Brand; Charlotte Pike; Chris Sergeant; Chris Grzesiok; Rosalind M. Wright; Adam T. Piper (Journal of Fish Biology, 2025)
River connectivity is crucial for the European eel ( Anguilla anguilla ) to complete its complex life cycle, which is vital for upstream recruitment to the declining population of this critically endangered catadromous fish. Eel passes, or ladders, are frequently installed on riverine structures, such as dams and weirs, to mitigate barrier effects and restore connectivity for upstream migrating eel. Efforts to optimise the effectiveness of passes have previously focused on the ascent section, quantifying the effects of climbing substrate, longitudinal slope, lateral slope and flow rate. However, conditions at the pass crest also impact the rapidity and success of upstream movements. Using controlled experiments and custom‐built eel passes with contrasting crest shapes (curved vs. sloped) and flow directions (ascending vs. descending), we quantified the effect of crest conditions on the attempt success, passage efficiency and speed of ascending juvenile eel. Only three of the four treatments (sloped ascending, curved descending and curved ascending) demonstrated passage efficiencies significantly greater than 50%. Transit speed at the crest was significantly quicker (~3.5 min) in passes with a curved crest shape and ascending flow compared to the control. Our findings indicate that simple modifications to the shape of the pass crest and the configuration of flow delivery can help minimise delay and enhance passage efficiency. This, in turn, will increase upstream migration success and contribute to conservation and management goals, such as the EU Eel Regulation and The Eels (England and Wales) Regulations 2009.

Rapid Ocean Warming Drives Sexually Divergent Habitat Use in a Threatened Predatory Marine Ectotherm - Lucy R. Mead; Adam Piper; David Jiménez Alvarado; Eva Meyers; Joanna Barker; Hector Toledo‐Padilla; Edy Herraiz; Alberto F. Campoamor; Michael Sealey; Maria Belén Caro; Tomàs Bañeras; Charlotte Pike; et al. (Global Change Biology, 2025)
Climate change poses one of the greatest threats to marine ecosystems worldwide, altering physical, chemical, and biological processes at unprecedented rates. Severe impacts on marine species and habitats have been extensively documented, with shifts in phenology, spatial distribution, and migratory behaviour increasingly pervasive. However, there is a lack of species‐specific data examining responses and adaptation to rapid warming and environmental extremes, especially for marine ectotherms. In this study, we investigate the broad‐scale environmental drivers of distribution in a Critically Endangered ectothermic marine predator, the angelshark Squatina squatina , and report on a behavioural anomaly observed in 2022. Between 2018 and 2023, 112 adult S. squatina were tracked using acoustic telemetry in La Graciosa Marine Reserve in the Canary Islands. Relationships between seasonal presence of S. squatina and remotely sensed environmental parameters were examined with Boosted Regression Tree and Generalised Additive Modelling. Major sex differences were found, with female sharks strongly influenced by environmental conditions and particularly sensitive to temperature, with a possible upper thermal threshold close to 22.5°C. Peak sea surface temperature in the study area increased from 22.99°C to 23.81°C, and the number of days above 22.5°C nearly tripled. Absence of females during the 2022 breeding season coincided with widespread thermal anomalies across the Northeast Atlantic Ocean, with unusually high temperatures persisting later into the year. We conclude that this potentially disrupted seasonal thermal cues for S. squatina movement, leading to sexually divergent habitat use. Given the warming projected for this region, thermal thresholds may increasingly be exceeded, and key areas may become inhospitable for female S. squatina , which is of huge concern for this already highly threatened species. These findings highlight the urgency of identifying species‐specific environmental tolerances and incorporating these into conservation so that management remains ecologically relevant in a rapidly warming ocean.

The Seaward Migration of European Eel at a Continental Scale: A Europe‐Wide Biotelemetry Meta‐Analysis - Pieterjan Verhelst; David Righton; Kim Aarestrup; Pedro R. Almeida; Tea Bašić; Jonathan D. Bolland; Liam Carter; Johan Coeck; José Lino Costa; Justas Dainys; Jan Grimsrud Davidsen; Isabel Domingos; et al. (Fish and Fisheries, 2025)
The European eel ( Anguilla anguilla L.) has a catadromous life cycle, with a single panmictic population that colonises continental Europe and northern Africa yet migrates 5000 to 9000 km to spawn in the Atlantic Ocean. It is unknown how this continental migration is organised so individual eels arrive in time for spawning with conspecifics. This meta‐analysis combined tracking data from 18 water bodies in freshwater and transitional systems distributed along the southwest‐northeast axis of Europe, resulting in a dataset of 2306 eels, making it the most comprehensive in terms of geographical coverage and number of eels tagged. The eels were tracked using acoustic telemetry and the Nedap Trail System and allowed us to study the eel's migration phenology at a continental scale. The findings reveal that the day when eels arrive at sea varies significantly with latitude, with northern eels arriving earlier. Migration speed differs between tidal and non‐tidal habitats, suggesting that tidal currents facilitate faster movement. However, despite these patterns, we observed substantial variability in arrival at sea time and migration speed within water bodies, suggesting that the eel's migration phenology is considerably plastic. The presence of water regulating structures such as weirs, pumping stations and hydropower plants can impact migration timing and speed, potentially delaying eels, but is likely dependent on local hydrological conditions which can be water body specific.

What acoustic telemetry can and cannot tell us about fish biology - David M. P. Jacoby; Adam T. Piper (Journal of Fish Biology, 2025)
Acoustic telemetry (AT) has become ubiquitous in aquatic monitoring and fish biology, conservation, and management. Since the early use of active ultrasonic tracking that required researchers to follow at a distance their species of interest, the field has diversified considerably, with exciting advances in both hydrophone and transmitter technology. Once a highly specialized methodology, however, AT is fast becoming a generalist tool for those wishing to study or conserve fishes, leading to diversifying application by non‐specialists. With this transition in mind, we evaluate exactly what AT has become useful for, discussing how the technological and analytical advances around AT can address important questions within fish biology. In doing so, we highlight the key ecological and applied research areas where AT continues to reveal crucial new insights and, in particular, when combined with complimentary research approaches. We provide a comprehensive breakdown of the state of the art for applications of AT, discussing the ongoing challenges, where its strengths lie, and how future developments may revolutionize fisheries management, behavioral ecology and species protection. Through selected papers we illustrate specific applications across the broad spectrum of fish biology. By bringing together the recent and future developments in this field under categories designed to broadly capture many aspects of fish biology, we hope to offer a useful guide for the non‐specialist practitioner as they attempt to navigate the dizzying array of considerations and ongoing developments within this diverse toolkit.

Migration patterns, habitat use and genetic origins of sea trout (Salmo trutta) in Norfolk chalk streams: implications for management of a mixed stock fishery - Adam T. Piper; Paula J. Rosewarne; Dorte Bekkevold; Jonathan Grey; Abbie Nye; Rosalind M. Wright (Aquatic Sciences, 2025)
Sea trout, the anadromous ecotype of the species Salmo trutta , are subject to multiple threats, including exploitation and aquaculture impacts in the marine environment, habitat fragmentation and pollution in freshwaters, loss of genetic resilience due to interbreeding with hatchery strains and environmental change. Small streams contribute relatively little biomass to European sea trout stocks but are thought to be important in maintaining genetic diversity and therefore wider population resilience. The current study combined data from acoustic telemetry, stable isotopes, genetics and scalimetry to assess the current status of sea trout in the rivers Stiffkey and Glaven, two locally important chalkstreams in East Anglia, UK, to provide an evidence base for future management. The incidence of anadromy was low, and most sea trout were near migrants, residing in the lower reaches of rivers and close to the tidal outfalls. A small number migrated to the North Sea where they were vulnerable to exploitation in the coastal fishery, which comprises a mixed stock. Straying between the two rivers was recorded among 10% of sea trout, leading to apparent high gene flow. Nonetheless, genetic data also demonstrated structuring of River Glaven trout into two distinct groups. Quantification of patterns of freshwater and estuarine habitat use, and of passage at cross-channel obstructions, was used to identify where remedial measures such as habitat restoration would be most effectively targeted. Findings are discussed in the context of local supplementary stocking and the potential impact of the nearshore fishery on limited and vulnerable small stream anadromous trout populations.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Correction: Environmental influences on the phenology of immigrating juvenile eels over weirs at the tidal limit of regulated rivers - Rose M. Boardman; Adrian C. Pinder; Adam T. Piper; Catherine Gutmann Roberts; Rosalind M. Wright; J. Robert Britton (Hydrobiologia, 2024)

Environmental influences on the phenology of immigrating juvenile eels over weirs at the tidal limit of regulated rivers - Rose M. Boardman; Adrian C. Pinder; Adam T. Piper; Catherine Gutmann Roberts; Rosalind M. Wright; J. Robert Britton (Hydrobiologia, 2024)
Recruitment of the catadromous and critically endangered European eel Anguilla anguilla in Europe has declined substantially since the 1980s, with considerable knowledge gaps remaining in many aspects of their life cycle. The aim was to assess eel migration phenology in three regulated rivers in England between 2009 and 2019 through analyses of eel numbers using passes at their tidal limits, with calculation of the annual timings of migration initiation (10% of all eels passed, T 10 ), peak (50%, T 50 ) and conclusion (90%, T 90 ). Across the three rivers, T 10 varied between Julian Day (‘Day’) 94 and 173. Years of earlier T 10 had significantly earlier T 50 , where T 50 varied between Day 105 and 200. The considerable inter-annual variability in migration timings was associated with environmental variables; earlier T 10 and T 50 occurred in years of warmer river temperatures (RTs) and cooler sea surface temperatures (SST), and in years where RTs were higher than SSTs. No environmental variables were significant predictors of T 90 . These results indicate that whilst there is annual variability in the timing of eel migration initiation and peak into freshwaters, this variability is predictable according to differences in environmental conditions. As many of these conditions associated with annual variability in temperature and precipitation then climate change has the potential to shift these migration timings.

Variability in the duration and timing of the estuarine to freshwater transition of critically endangered European eel Anguilla anguilla - Rose M. Boardman; Adrian C. Pinder; Adam T. Piper; Catherine Gutmann Roberts; Rosalind M. Wright; J. Robert Britton (Aquatic Sciences, 2024)
The European eel ( Anguilla anguilla L.) is a critically endangered catadromous fish. Their inshore and in-river arrival as glass eel and elvers is an important stage of their life cycle, marking the transition from marine to freshwater habitats. Considerable knowledge gaps remain on the temporal and spatial patterns of this transition period to freshwater residency. Stable isotope (SI) analysis (δ 13 C, δ 15 N) was used to assess the timing and duration of the marine to freshwater transition among glass eels and elvers migrating upstream of the weirs at, or just upstream of, the tidal limit of four English rivers. (Parrett, Frome, Piddle, Chelmer). Variability in SI was low in the Parrett and Frome, resulting in narrow isotopic niches, but was high in the Piddle and Chelmer, resulting in wider niches. The Parrett and Frome data were then used to train a discriminant function analysis (DFA) model to classify eels as ‘marine’, ‘freshwater-established’ and ‘transitioning’. When applied to the Piddle and Chelmer eel SI data, only a small proportion of eels were classified as marine and transitioning, with most being freshwater established. These results suggest that most eels present in the lower reaches rivers have been present for sufficient time for their SI values to represent feeding on local prey resources, with relatively few eels being newly arrived from the marine environment. The transition of eels from marine to freshwater in this species can therefore be prolonged, with many ascending rivers at least one winter after their initial arrival.

The Eel Ascending: The Influence of Lateral Slope, Climbing Substrate and Flow Rate on Eel Pass Performance - Adam T. Piper; Paula J. Rosewarne; Charlotte Pike; Rosalind M. Wright (Fishes, 2023)
Optimising the design of passage facilities to restore fluvial connectivity for juvenile European eel (Anguilla anguilla) is a key priority within conservation efforts for the species, across the majority of its freshwater range. Employing an experimental setup that simulated gravity-fed upstream eel passes, this study demonstrated that novel V-profile passes, which incorporate two lateral slopes (15°), performed better than laterally flat passes over the flow rates tested (0.2–0.6 L s−1). For the small eel size used (60–80 mm length), the bristle substrate consistently outperformed studs, but the lateral slope had a greater effect on passage metrics than the substrate choice. Our findings strongly support the use of V-shaped channels for upstream migrating eel at fish passage facilities, particularly in scenarios where flow rates may be elevated and/or fluctuating, such as for gravity-fed passes.

Effects of preservation by ethanol on δ 13 C and δ 15 N of three tissues of the critically endangered European eel Anguilla anguilla - Rose M. Boardman; Adrian C. Pinder; Adam T. Piper; Catherine Gutmann Roberts; Rosalind M. Wright; John Robert Britton (Journal of Fish Biology, 2023)
The temporal effects of ethanol preservation on the δ 13 C and δ 15 N values of tissues excised from European eel Anguilla anguilla were assessed. Preservation significantly enriched 13 C values of fin and mucus but not dorsal muscle. The 13 C enrichment occurred in the initial 15 days of preservation and was independent of initial eel mass. Tissue preservation effects on δ 15 N values were negligible. These tissue‐specific isotopic shifts should be considered when ethanol‐preserved eel samples are used.

Spatiotemporal distributions of mammals occurring in an agro‐prairie ecosystem - Gabriela Palomo‐Munoz; Ty J. Werdel; Colleen W. Piper; Matthew S. Peek; Andrew M. Ricketts; Adam A. Ahlers (Ecology, 2023)
Anthropogenic activities since the European colonization of the North American Great Plains have drastically altered landscape composition and configuration, subsequently affecting native biodiversity. These contemporary human‐modified landscapes may affect mammal species' distributions, diel activity patterns, habitat use, and interspecific interactions, though a better understanding of these effects on mammals occurring in remaining prairie landscapes is needed. To fill this gap, we surveyed 381 randomly selected sites in 2018, 2019, and 2020 using motion‐sensing camera traps across the western part of the US state of Kansas (7,160,077 ha). Sites were separated by ≥2 km ( = 8.16 km, SD = 3.61), and cameras were secured to a metal post 40 cm above ground and randomly oriented toward the north or south. We placed an olfactory attractant (mixture of skunk essence and petroleum jelly) on a wooden stake 3 m in front of each camera. Cameras were in place at each site for 28 consecutive days for each year. We manually identified all mammal species detected at each site, collating these data into a database that included taxonomic information for 14 families of mammals (Antilocapridae, Bovidae, Canidae, Cervidae, Cricetidae, Dasypodidae, Didelphidae, Erethizontidae, Felidae, Heteromyidae, Leporidae, Mephitidae, Mustelidae, Procyonidae, Sciuridae, and Muridae) comprising 28 total species. We recorded 31,178 mammal photographs (nonindependent events) over 27,954 camera trap nights during 2018 ( n = 10,351), 2019 ( n = 9478), and 2020 ( n = 8125). Additionally, we included the time and date of each photocapture. Moreover, we gathered survey‐specific data useful for modeling species‐specific detection along with site‐level habitat composition data taken at each site each year. These data will be useful for examining habitat use, species distributions, diel activity patterns, and spatiotemporal interactions between species and across guilds of mammals occurring in a rapidly changing agro‐prairie ecosystem. There are no copyright restrictions, but we ask researchers to cite this paper when using these data for publication.

The drivers of anguillid eel movement in lentic water bodies: a systematic map - Michael J. Williamson; David M. P. Jacoby; Adam T. Piper (Reviews in Fish Biology and Fisheries, 2023)
Anguillid eels are near globally distributed catadromous fishes with marine spawning areas and inshore and inland growth areas in both lotic (rivers, estuaries) and lentic (lakes, ponds, lagoons) water bodies. As predators, anguillid eels play an important ecological role in both marine and freshwater systems, and several species are harvested commercially for food. However, some of the more widely distributed species have undergone severe declines in recruitment and their population status is now of significant concern. Given the multiple and lengthy migrations undertaken by anguillid eels, understanding of the drivers of movement is fundamental for species conservation and management. Yet, despite the importance of lentic systems to their ecology, most studies on anguillid eel movement have been conducted in lotic systems. Given that key influences on eel migration in lotic water bodies, such as fluctuations in flow and water temperature, may be minimised in lentic environments, the transferability of findings between lotic and lentic systems cannot be assumed. A systematic map was constructed to synthesise current knowledge on the extrinsic and intrinsic drivers of anguillid eel movement in lentic systems. The current state of knowledge of the drivers of eel movement in lentic systems is presented and compared to the relatively well-understood drivers of movement in lotic systems. We also discuss current knowledge gaps and limitations, and identify key future research requirements to inform the management and conservation of anguillid eels in understudied lentic systems. Graphical abstract

Strategic grassland conservation for swift foxes in multi-use landscapes - Ty J. Werdel; Colleen W. Piper; Andrew M. Ricketts; Matthew S. Peek; Dan S. Sullins; Adam A. Ahlers (Biological Conservation, 2023)

Non‐lethal sampling for the stable isotope analysis of the critically endangered European eel Anguilla anguilla : how fin and mucus compare to dorsal muscle - Rose M. Boardman; Adrian C. Pinder; Adam T. Piper; Catherine Gutmann Roberts; Rosalind M. Wright; J. Robert Britton (Journal of Fish Biology, 2022)
Ecological studies on the critically endangered European eel Anguilla anguilla often incorporate stable isotope analysis that typically uses dorsal muscle sampled from euthanised eels. To minimise the lethal sampling of imperilled populations, fin tissue and/or epidermal mucus can provide non‐lethal alternatives to muscle. The results here indicate that δ 13 C and δ 15 N values of both eel fin and mucus are not significantly different from those of muscle and can be applied directly in comparative SI studies.

Important questions to progress science and sustainable management of anguillid eels - David Righton; Adam Piper; Kim Aarestrup; Elsa Amilhat; Claude Belpaire; John Casselman; Martin Castonguay; Estibaliz Díaz; Hendrik Dörner; Elisabeth Faliex; Eric Feunteun; Nobuto Fukuda; et al. (Fish and Fisheries, 2021)
Anguillid eels are found globally in fresh, transitional and saline waters and have played an important role in human life for centuries. The population status of several species is now of significant concern. The threats to populations include direct exploitation at different life stages, blockages to migratory routes by dams and other structures, changes in river basin management that impact habitat carrying capacity and suitability, pollution, climate change, diseases and parasites. While much has been done to understand eel biology and ecology, a major challenge is to identify the key research and management questions so that effective and targeted studies can be designed to inform conservation, management and policy. We gathered 30 experts in the field of eel biology and management to review the current state of knowledge for anguillid eel species and to identify the main topics for research. The identified research topics fell into three themes: (a) Lifecycle and Biology; (b) Impacts and (c) Management. Although tropical anguillid eels are by far the least well understood, significant knowledge gaps exist for all species. Considerable progress has been made in the last 20 years, but the status of many species remains of great concern, particularly for northern temperate species. Without improved engagement and coordination at the regional, national and international level, the situation is unlikely to improve. Further, adaptive management mechanisms to respond to developments in science, policy and our knowledge of potential threats are required to ensure the future of these important and enigmatic species.

Spatial and temporal behavioural patterns of the European eel Anguilla anguilla in a lacustrine environment - Tea Bašić; Luke Aislabie; Mark Ives; Lenka Fronkova; Adam Piper; Alan Walker (Aquatic Sciences, 2019)